2021
DOI: 10.1002/ece3.7797
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine results in misleading conclusions on fish behavior

Abstract: Freshwater ecosystems contain 41% of the world's known fish species (Daily, 1997). Unfortunately, freshwater biodiversity faces many threats. Aquatic environments, and especially small bodies of the water, are currently one of the most degraded types of ecosystems (WWF Living Planet Report, 2020). Pharmaceuticals are a threat to modern biodiversity. The reason is permanent presence of pharmaceutical substances in the freshwater ecosystems (Hughes et al., 2013). Among these medicines, there is the commonly used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
0
4
0
1
Order By: Relevance
“…This individual behavioural variance, like stress coping styles (SCS), has been associated with personality aspects ( Tudorache et al, 2015 ; Fatsinia et al, 2020 ; Carbonara et al, 2019 ). Indeed, not all individuals within a species react the same way when subjected to the same conditions, even if they share the same age, size, sex, and place of origin ( Grzesiuk and Pawelec, 2021 ). This variation in individual sensitivity may affect susceptibility to disease and/or environmental contaminants ( Demin et al, 2019 ; Wong et al, 2019 ).…”
Section: Ssris and Their Impact On Fish Personality/coping Stylesmentioning
confidence: 99%
See 2 more Smart Citations
“…This individual behavioural variance, like stress coping styles (SCS), has been associated with personality aspects ( Tudorache et al, 2015 ; Fatsinia et al, 2020 ; Carbonara et al, 2019 ). Indeed, not all individuals within a species react the same way when subjected to the same conditions, even if they share the same age, size, sex, and place of origin ( Grzesiuk and Pawelec, 2021 ). This variation in individual sensitivity may affect susceptibility to disease and/or environmental contaminants ( Demin et al, 2019 ; Wong et al, 2019 ).…”
Section: Ssris and Their Impact On Fish Personality/coping Stylesmentioning
confidence: 99%
“…Although it is well established that SSRIs can interfere with fish behaviour, data on differential responses to this type of antidepressant depending on fish personality, is very limited ( Salahinejad et al, 2022 ). In humans, the suppression of certain personality traits due to SSRI treatment has been reported to occur in some cases ( Grzesiuk and Pawelec, 2021 ).…”
Section: Ssris and Their Impact On Fish Personality/coping Stylesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ayrıca çevresel fluoksetine maruz kalmanın, lepisteslerde hayatta kalmayı azalttığı, anormal davranışları artırdığı ve yırtıcı hayvan kaçış tepkilerini geciktirdiği bulunmuştur. 11 Fluoksetinin davranışsal etkilerini değerlendirmek için erişkin medaka balıklarına fluoksetinin kronik uygulanmasından sonra kaygıyla ilgili ve sosyal davranışlarla ilgili gözlemler yapılmıştır. Kronik fluoksetinin uygulamasının balıklarda anksiyolitik tepkilere neden olduğu gözlenmiştir.…”
Section: Fluokseti̇nunclassified
“…Although there are few studies on the effects of fluoxetine on nontarget organisms, the results show hazards at different levels. For instance, Grzesiuk and Pawelec (2021) found a delay in the response time to a possible dangerous situation (e.g. a predator) in Neogobius fluviatilis (monkey goby) and Duarte et al (2020) showed that fluoxetine was accumulated in fish tissue (Argyrosomus regius; Salmon-bass) causing DNA damage in liver cells, affecting growth, and triggering antioxidant defence responses.…”
Section: Introductionmentioning
confidence: 99%